Heavy Metals Phytoremidiation Potential of Napier Grass Cultivated on Tannery Sludge in Bangladesh (Journal of Engineering Science, 2021)
Phytoremediation is a cost effective and eco-friendly method for cleanup of contaminated soil. This study focused on the assessment of phytoremediation potential of Napier grass (Pennisetum purpureum) and Indian mastered (Brassica juncea) yielding in tannery sludge. Initial characterization of tannery sludge showed a high concentration of chromium, lead, copper and zinc which were 6845.5±50.2, 73±2.5, 93±1.5 and 29±2.5 mg/kg, respectively. Both seeds of these plants were sown on tannery sludge kept in baskets and harvested after 8 and 12 weeks of plantation. Analysis indicated that both Napier grass and Indian mustard accumulated heavy metals in the order of Cr>Zn>Cu>Pb at different parts of these plants. Transfer factor (TF) for both plants were greater than 1 for Cu, Zn, Pb though it was less than 1 for Cr. Indian mustard accumulated highest concentration of Cr, Cu, and Pb whereas Napier grass showed highest Zn uptake and good Cr and Cu accumulation capacity. The uptake rate of Cr increased in Napier grass with the increase of plant age. Moreover, Napier grass is one of the rapid yielding tropical grasses and can retain for a longer period than Indian mustard for that attribute, it may accumulate more heavy metals than Indian mustard within its life span. Both of these plants can be used for remediating heavy metals from contaminated tannery sludge.Journal of Engineering Science 12(1), 2021, 35-41